Determinants of tourism in the Bay of Camamu-BA for Tourism Planning and local development - Borges, Carlos Henrique Leite; Guzmán, Sócrates Jacobo Moquete; Midlej, Moema Maria Badaró Cartibani (Revista Turismo em Análise, 2013)
This study aimed to assess the tourism from the perspective of the visitors and the local community, thus enabling to establish the main determinants of tourism and ultimately the development of an index of adequacy of its components to local development. It was used the multivariate analysis, through factor analysis as a way to determine the factors of the local tourist and its index. The results revealed a framework where components of the local tourist indicated a certain fragility, a fact also reflected in the proposed index, and the need to improve the quality of some factors and other urgent interventions. So, visitors and community approach in their assessments, with some specifics regarding the characteristics of place that must also be considered in the planning of tourism and its development.